Bulan Sabit di Atas Lampion: Dinamika dan Kehidupan Sosial Tionghoa Muslim di Surakarta Tahun 1982-2013 - Ryas Basmala (Departement of History and Islamic Civilization, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2021)
This study explains how the Chinese in Surakarta have established themselves to convert to Islam. While in other big cities there are already associations to accommodate Chinese Moslem people, but in Surakarta, which is a big city, there is no forum to gather these people. This study uses four main steps of the historical method, namely: (1) heuristics, (2) source criticism, (3) interpretation, and (4) historiography. The result of this research is that the Chinese descent converted to Islam due to three reasons, the first is because of marriage, the second is guidance, and the third is because they follow the religion of their parents or are Muslim since birth. Although there is no PITI (Indonesian Chinese Islamic Association) in Surakarta, in Surakarta there is an organization called Mualaf Center Soloraya, this organization can be used to add Islamic insight to people who have converted to Islam.